Research on orthogonal multi-carrier underwater acoustic communication system based on fractional Fourier transform - Yi-lin WANG; Yun CHEN; Jing-wei YIN; Ping CAI; Yi-meng ZHANG (Tongxin xuebao)
Aimed at the traditional OFDM communication system fails when the channel was frequency-selective,rapidly fading and had the Doppler effects,resulting in inter-carrier interference,a orthogonal multi-carrier system for underwater acoustic communication was proposed,which employed orthogonal signal basis of the chirp type corresponding to the fractional Fourier transform (FRFT) signal basis.The scheme used the orthogonal LFM signal as sub-carrier to modulate,which had same chirp rate but different center frequency with overlapped bandwidth,and used fractional Fourier transform for modulation and demodulation method to transmit information.For suppression of the multi-paths channel effect,the guard interval (GI) was used between signal data frame.And the position correction in fractional domain method combining with QDPSK was proposed to suppress the Doppler effects,which simplified the system complexity.The communication scheme had the characteristic of high communication rate,and the maximum rate was up to 3 600bit/s.The effectiveness and reliability of this system was verified through a large number of simulation and lake experiments.